2011
DOI: 10.1159/000326781
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Cognitive Function by Clock Drawing in Older Adults

Abstract: Aims: To test the hypotheses that performance on a clock-drawing task (CDT) diminishes over time and that poor performance is associated with development of dementia and reduced survival. Methods: Participants in the population-based Leisure World Cohort Study were asked to complete a CDT in follow-up questionnaires mailed in 1992 and 1998. Dementia status was determined using in-person evaluations, follow-up questionnaires, hospital data, and death certificates. Results: Of the 4,842 cohort members (mean age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 54 publications
0
17
2
Order By: Relevance
“…Studies in older community dwellers with up to 7 years of follow-up consistently report the CDT as a predictor of all-cause mortality risk independently of health confounders [30,31,32,33]. By contrast, the only evidence for CDT as a predictor of nonlethal outcomes in older persons included residents from a retirement community, and an association with the 2.5-year risk of needing 24-hour care was found [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in older community dwellers with up to 7 years of follow-up consistently report the CDT as a predictor of all-cause mortality risk independently of health confounders [30,31,32,33]. By contrast, the only evidence for CDT as a predictor of nonlethal outcomes in older persons included residents from a retirement community, and an association with the 2.5-year risk of needing 24-hour care was found [31].…”
Section: Discussionmentioning
confidence: 99%
“…None of these investigations, however, included assessment of the physical phenotype. Moreover, most of them used nonstandard CDT protocols with no predefined standard cutoffs [30,31,33]. One study [32] used Royall's CLOX, which is reported to have the highest sensitivity for executive impairment [13].…”
Section: Discussionmentioning
confidence: 99%
“…CDT is a neuropsychological tool to assess a wide range of higher-level cognitive abilities required simultaneously for its successful completion, including language comprehension, visuospatial abilities, working memory, attention and abstract thinking 27. CDT is a useful instrument to identify subjects at risk of cognitive decline and dementia 28. We used a validated Spanish version ranging from 0 to 7 29…”
Section: Methodsmentioning
confidence: 99%
“…We used a validated Spanish version ranging from 0 to 7 (del Ser Quijano et al 2004). Both cognitive tests are valid indicators of cognitive impairment (Crook et al 1986;Paganini-Hill and Clark 2011). Researchers who assessed the outcome were blinded to group assignment.…”
Section: Cognitive Assessmentmentioning
confidence: 99%